Transference of individual authorial metaphor as a component of idiostyle in adapted English literary works (on the example of S. Maugham’s stories) - Novikova N. A., Beresnev A. A. (Human and society, 2017)
the article deals with the metaphor, as an indicator of authorial personality and a component of the style. It examines the problem of idiostyle misrepresentation while adapting original texts. This paper also focuses on the degree to which metaphors can be preserved while adapting texts.
Keywords: адаптация; идиостиль; adaptation; индивидуально-авторская метафора; адаптированный текст; idiostyle; individual and authorial metaphor; adapted text